2014
DOI: 10.1002/em.21886
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage in disease—Insights gained from base excision repair glycosylase‐deficient mouse models

Abstract: Cellular components, including nucleic acids, are subject to oxidative damage. If left unrepaired, this damage can lead to multiple adverse cellular outcomes, including increased mutagenesis and cell death. The major pathway for repair of oxidative base lesions is the base excision repair pathway, catalyzed by DNA glycosylases with overlapping but distinct substrate specificities. To understand the role of these glycosylases in the initiation and progression of disease, several transgenic mouse models have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 139 publications
(243 reference statements)
1
42
0
Order By: Relevance
“…Since we have previously reported that Ogg1 -/- mice have impaired insulin sensitivity [28], and given that OGG1 is involved in repair of both genomic, as well as mtDNA [5,49], we were interested in determining the role of OGG1 deficiency on mitochondrial content in the muscle of these animals. There were no differences in total content of mtDNA between genotypes, as measured by qPCR against several different mtDNA target regions (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Since we have previously reported that Ogg1 -/- mice have impaired insulin sensitivity [28], and given that OGG1 is involved in repair of both genomic, as well as mtDNA [5,49], we were interested in determining the role of OGG1 deficiency on mitochondrial content in the muscle of these animals. There were no differences in total content of mtDNA between genotypes, as measured by qPCR against several different mtDNA target regions (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
“…We postulate that increased levels of 8-oxoG in AgNP-treated wild type mice is in part due to downregulation of DNA glycosylases that are involved in the repair of 8-oxoG. Ogg1, Neil1, and Neil2 are bifunctional DNA glycosylases with DNA glycosylase and AP lyase activities and have overlapping physiological substrates (Hazra et al 2007; Jacobs and Schar 2012; Sampath 2014). The common substrates recognized by Ogg1, Neil1, and Neil2 are 8-oxoG and FapyG.…”
Section: Discussionmentioning
confidence: 99%
“…8-Oxoguanine DNA glycosylase 1 (OGG1) is a base excision repair (BER) enzyme that removes oxidatively damaged guanine from double stranded DNA (Hirano 2008; Sampath 2014). OGG1 is a bifunctional glycosylase that exhibits DNA glycosylase and apurinic/apyrimidinic (AP) lyase activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human NTHL1 enzyme is a bifunctional glycosylase involved in the excision of oxidized DNA bases such as Tg, 5‐hydroxycytosine (5‐hC), 5‐hydroxyuracil (5‐hU), and the ring‐opened 2,6‐diamino‐4‐hydroxy‐5‐formamidopyrimidine (Fapy) lesions (Table ). Whereas human NTHL1 is found in both nucleus and mitochondria, mouse Nth1 translocates primarily to the mitochondria [Sampath, ].…”
Section: Dna Glycosylase Families In the Mitochondria: Biochemical Fumentioning
confidence: 99%